Study on Practical Issues for the State Estimation of the Automatic Voltage Control (AVC) System - Lin Xu (Institute of Advanced Engineering and Science, 2013)
The state estimation is an important part of the automatic voltage control (AVC) system, and it is the basis of the advanced software application for the electric power systems (EPSs). This paper presents the status quo of the current state estimation mathematical model and the actual grid state estimation applications. The actual AVC system network modeling and model validation, pre-processing and other related issues are discussed, and the methods for detection and identification of bad data are presented. Besides, the debugging method of state estimation for enhancing practical pass-rate is proposed. Finally, the state estimation of the actual system is validated, and the results show that the state pass-rate is more than 99%, which has important significance for the AVC control practitioners and power flow dispatchers.DOI: http://dx.doi.org/10.11591/telkomnika.v11i3.2256